Association between C-reactive protein levels and physical fitness in 7 to 9 year old children at poor elementary schools in Surakarta, Indonesia - Lilisianawati Lilisianawati; Endang Dewi Lestari; Diana Mayasari Hadianto; Maria Galuh Kamenyangan Sari; Leilani Lestarina; Harsono Salimo (Paediatrica Indonesiana, 2009)
Background  Data  regarding inflammatory factors  in  children arenot  so  well developed  as  in adults. Higher levels  of  physical fitnessmay be helpful in modifying the low-grade inflammatory state  thatis  indexed  by  C-reactive protein (CRP) levels.Objective  To  evaluate the association  of  physical fitness with  CRPlevels in children  and  to identify the possible related factors.Methods  This  cross-sectional study was  conducted  at  poorelementary schools in Surakarta, Indonesia using a group  of  217underweight children aged from 7 to 9 years old. Physical fitnesswas assessed using a modified Harvard Step Test.  CRP  levels weremeasured using a high-sensitivity  assay.  The  association betweenphysical fitness and  CRP  level was assessed using linear regressionanalysis. Multivariate analyses were used to adjust covariates,and statistical analyses were performed using SPSS for Windowssoftware version 15.0.Results  Subjects were 48% female  and  52% male, and elevenchildren (5%) had a  CRP  level  >  5 mg/L. Mean fitness level  andCRP  level did not differ  by  age and gender. Fitness level was notinversely correlated with  CRP  (r=0.10,  P=0.14).  Physical fitnesswas significantly correlated with BMI  (r=0.14;  P=0.04),  physicalactivity  [0R=3.3  (95% CI  1.7  to 6.4)], and fat intake  [0R=0.5(95%  CI  0.2 to 0.9) ].Conclusion  These findings indicate  that  physical fitness  is  notinversely correlated to  CRP  levels in children. However, ourstudy reveased  an  association between high fat intake and lowphysical fitness as well  as  a significant association  betweenhigh physical activiry and physical fitness.